Funding AIDS programmes in the era of shared responsibility: an analysis of domestic spending in 12 low-income and middle-income countries. Issue 1 (January 2015) - Resch, Stephen; Ryckman, Theresa; Hecht, Robert
Summary Background As the incomes of many AIDS-burdened countries grow and donors' budgets for helping to fight the disease tighten, national governments and external funding partners increasingly face the following question: what is the capacity of countries that are highly affected by AIDS to finance their responses from domestic sources, and how might this affect the level of donor support? In this study, we attempt to answer this question. Methods We propose metrics to estimate domestic AIDS financing, using methods related to national prioritisation of health spending, disease burden, and economic growth. We apply these metrics to 12 countries in sub-Saharan Africa with a high prevalence of HIV/AIDS, generating scenarios of possible future domestic expenditure. We compare the results with total AIDS financing requirements to calculate the size of the resulting funding gaps and implications for donors. Findings Nearly all 12 countries studied fall short of the proposed expenditure benchmarks. If they met these benchmarks fully, domestic spending on AIDS would increase by 2·5 times, from US$2·1 billion to $5·1 billion annually, covering 64% of estimated future funding requirements and leaving a gap of around a third of the total $7·9 billion needed. Although upper-middle-income countries, such as Botswana, Namibia, and South Africa, would become financially self-reliant, lower-income countries, such as Mozambique and Ethiopia, would remain heavily dependent on donor funds. Interpretation The proposed metrics could be useful to stimulate further analysis and discussion around domestic spending on AIDS and corresponding donor contributions, and to structure financial agreements between recipient country governments and donors. Coupled with improved resource tracking, such metrics could enhance transparency and accountability for efficient use of money and maximise the effect of available funding to prevent HIV infections and save lives. Funding US Centers for Disease Control and Prevention.